Glucocorticoids increase the Na+-H+ exchange and decrease the Na+ gradient-dependent phosphate-uptake systems in renal brush border membrane vesicles. - Freiberg, J M (1982)
The glucocorticoid dexamethasone, but not the mineralocorticoid aldosterone, increased amiloride-sensitive Na+-H+ exchange activity in rat proximal tubule brush border vesicles. Na+ uptake, independent of amiloride, was not affected. The glucocorticoid decreased the Na+ gradient-dependent phosphate uptake. Uptake in the absence of a Na+ gradient was not inhibited. Dexamethasone did not affect the Na+ gradient-dependent D-glucose uptake. These findings are consistent with the effects of glucocorticoids in stimulating acid secretion and causing phosphaturia in man and animals and may identify the locus of action and suggest the mechanisms by which the hormones act.